2019
DOI: 10.4236/jcc.2019.77022
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Acceleration of Solving Heat and Mass Transfer Equations with the First Kind Boundary Conditions in Capillary Porous Radially Composite Cylinder Using Programmable Graphics Hardware

Abstract: With the latest advances in computing technology, a huge amount of efforts have gone into simulation of a range of scientific phenomena in engineering fields. One such case is the simulation of heat and mass transfer in capillary porous media, which is becoming more and more necessary in analyzing a number of eventualities in science and engineering applications. However, this procedure of numerical solution of heat and mass transfer equations for capillary porous media is very time consuming. Therefore, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Nowadays, very powerful resources exist to effi-ciently analyze and understand a complex set of heat and mass transfer problems. Recently, Narang et al [1] demonstrated that the GPU (Graphical Processing Unit) can be much faster than the CPU (Compute Processing Unit) in the area of numerical heat and mass transfer solutions. Furthermore, the experimental results obtained for a radially composite capillary porous cylinder indicate that the GPU-based implementation shows a significant performance improvement over the CPU-based implementation with maximum speedups of about 10 times.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, very powerful resources exist to effi-ciently analyze and understand a complex set of heat and mass transfer problems. Recently, Narang et al [1] demonstrated that the GPU (Graphical Processing Unit) can be much faster than the CPU (Compute Processing Unit) in the area of numerical heat and mass transfer solutions. Furthermore, the experimental results obtained for a radially composite capillary porous cylinder indicate that the GPU-based implementation shows a significant performance improvement over the CPU-based implementation with maximum speedups of about 10 times.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, sequential codes are used, but they are not adequate for parallelization. However, parallelization and high-performance computing resources have become fundamental strategies to improve numerical performance (see [3] and references therein). Notwithstanding this new paradigm, the procedure is not straightforward.…”
Section: Introductionmentioning
confidence: 99%